New BODIPY lipid probes for fluorescence studies of membranes - Boldyrev, Ivan A. (2007)
Many fluorescent lipid probes tend to loop back to the membrane interface when attached to a lipid acyl chain rather than embedding deeply into the bilayer. To achieve maximum embedding of BODIPY (4,4-difluoro-4-bora-3a,4a-diaza-s-indacene) fluorophore into the bilayer apolar region, a series of sn-2 acyl-labeled phosphatidylcholines was synthesized bearing 4,4-difluoro-1,3,5,7-tetramethyl-4-bora-3a,4a-diaza-s-indacene-8-yl (Me(4)-BODIPY-8) at the end of C(3)-, C(5)-, C(7)-, or C(9)-acyl. A strategy was used of symmetrically dispersing the methyl groups at BODIPY ring positions 1, 3, 5, and 7 to decrease fluorophore polarity. Iodide quenching of the phosphatidylcholine probes in bilayer vesicles confirmed that the Me(4)-BODIPY-8 fluorophore was embedded in the bilayer. Parallax analysis of Me(4)-BODIPY-8 fluorescence quenching by phosphatidylcholines containing iodide at different positions along the sn-2 acyl chain indicated that the penetration depth of Me(4)-BODIPY-8 into the bilayer was determined by the length of the linking acyl chain. Evaluation using monolayers showed minimal perturbation of <10 mol% probe in fluid-phase and cholesterol-enriched phosphatidylcholine. Spectral characterization in monolayers and bilayers confirmed the retention of many features of other BODIPY derivatives (i.e., absorption and emission wavelength maxima near 498 nm and ∼506−515 nm) but also showed the absence of the 620−630 nm peak associated with BODIPY dimer fluorescence and the presence of a 570 nm emission shoulder at high Me(4)-BODIPY-8 surface concentrations. We conclude that the new probes should have versatile utility in membrane studies, especially when precise location of the reporter group is needed.—Boldyrev, I. A., X. Zhai, M. M. Momsen, H. L. Brockman, R. E. Brown, and J. G. Molotkovsky. New BODIPY lipid probes for fluorescence studies of membranes.